TEACHERS' PERCEPTIONS REGARDING THE FLIPPED CLASSROOM METHOD OF USING GOOGLE CLASSROOM DURING THE COVID-19 PANDEMIC - Pawesti, Ezil (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2023)
This study focuses on identifying the teachers’ perceptions regarding the flipped classroom method of using Google Classroom during the Covid-19 pandemic at a high school in Jambi city. Since the flipped classroom method utilizes technology to help the material delivery and teaching-learning process, then this study describes teachers' perceptions, experiences, and feelings as a participant and reveal how they apply the flipped classroom method using technology during the pandemic. This study uses qualitative methods because the analysis is in the form of descriptions, not numbers. The data were utterances containing the perception of the English teacher about the flipped classroom method, and the data source was from 2 female teachers who use this method in four classes. Some data were collected through open interviews in an observational study. The study revealed that there were some obstacles and merits to flipped classroom method of using Google classroom. In addition, researchers also suggest additional applications to assist teachers in teaching using Google Classroom to overcome ineffectiveness in providing instant feedback to students.